Positive health effects of the natural outdoor environment in typical populations in different regions in Europe (PHENOTYPE): a study programme protocol. Issue 4 (16th April 2014) - Nieuwenhuijsen, Mark J; Kruize, Hanneke; Gidlow, Christopher; Andrusaityte, Sandra; Antó, Josep Maria; Basagaña, Xavier; Cirach, Marta; Dadvand, Payam; Danileviciute, Asta; Donaire-Gonzalez, David; Garcia, Judith; Jerrett, Michael; et al.
Abstract : Introduction: Growing evidence suggests that close contact with nature brings benefits to human health and well-being, but the proposed mechanisms are still not well understood and the associations with health remain uncertain. The P ositive H ealth E ffects of the N atural O utdoor environment in Ty pical P opulations in different regions in E urope (PHENOTYPE) project investigates the interconnections between natural outdoor environments and better human health and well-being. Aims and methods: The PHENOTYPE project explores the proposed underlying mechanisms at work (stress reduction/restorative function, physical activity, social interaction, exposure to environmental hazards) and examines the associations with health outcomes for different population groups. It implements conventional and new innovative high-tech methods to characterise the natural environment in terms of quality and quantity. Preventive as well as therapeutic effects of contact with the natural environment are being covered. PHENOTYPE further addresses implications for land-use planning and green space management. The main innovative part of the study is the evaluation of possible short-term and long-term associations of green space and health and the possible underlying mechanisms in four different countries (each with quite a different type of green space and a different use), using the same methodology, in one research programme. This type of holistic approach has not been undertaken before. Furthermore there are technological innovations such as the use of remote sensing and smartphones in the assessment of green space. Conclusions: The project will produce a more robust evidence base on links between exposure to natural outdoor environment and human health and well-being, in addition to a better integration of human health needs into land-use planning and green space management in rural as well as urban areas.